Taxonomy and distribution of Terebellides (Polychaeta: Trichobranchidae) in the northern South China Sea, with description of three new species - Zhang, Jinghuai; Hutchings, Pat (Zootaxa, 2018)
Benthic ecology monitoring in the northern South China Sea revealed many individuals of the polychaete genus Terebellides (Annelida), which are common in soft sediments in shallow waters (4.5–41.0 m). Three new species of Terebellides are described, including T. guangdongensis n. sp., T. yangi n. sp. and T. ectopium n. sp. Terebellides guangdongensis n. sp. is mainly found in Guangdong waters. Terebellides yangi n. sp. and T. ectopium n. sp. are mainly found in Beibu Gulf. A key to all described species of Terebellides from the Northwestern Pacific is given.